The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Frank, Tamara M.; Fine, Charles D.; Burdett, Eric A.; Cook, April B.; Sutton, Tracey T. (Frontiers in Marine Science, 2020)
The vertical and horizontal distributions of Euphausiacea in the northern Gulf of Mexico, including the location of the Deepwater Horizon oil spill, were analyzed from 340 trawl samples collected between April-June 2011. This study is the first comprehensive survey of euphausiid distributions from depths deeper than 1000 m in the Gulf of Mexico and includes stratified sampling from five discrete depth ranges (0-200m, 200-600m, 600-1000m, 1000-1200m, and 1200-1500m), and expands the depth ranges of 30 species. In addition, this study demonstrates significantly higher abundance and biomass of the euphausiid assemblage from slope vs. offshore stations, while the offshore assemblage was significantly more diverse. There is also some evidence for seasonality in reproduction amongst the seven species that had gravid females. Lastly, these data represent the first quantification of the euphausiid assemblage in the region heavily impacted by the Deepwater Horizon event, and as there are no pre-spill data, may serve as an impacted baseline against which to monitor changes in the euphausiid assemblage in the years following exposure to Deepwater Horizon oil and dispersants in the water column.